CASE-CONTROL STUDY OF RISK FACTORS FOR CANINE LEPTOSPIROSIS IN LIMA - Huerta M., Carlos (2013)
The aim of the present study was to describe potential risk factors for canine leptospirosis infections in patients of the Small Animal Clinic at the Veterinary School, San Marcos University, Lima, through a case-control study. Data from clinical records and serological test results from 2002 to 2007 were reviewed. Forty four cases and 394 controls were enrolled into the study. Collected data included sex, size, age, season of the year, and origin, and were analyzed by multivariable logistic regression. Risk factors related to the disease were: sex (male has double risk), size (bigger dogs have two times more risk) and age (risk increased with age).